KONSTRUKSI YURIDIS PENGATURAN BANTUAN JURU BAHASA BAGI TERDAKWA - Susilo, Erwin; Rafi, Muhammad (Faculty of Law, Universitas Pasundan, 2024)
The defendant has the right to present a defense, and to guarantee that the defendants must understand the facts that arise during trials. The Indonesian Criminal Procedure Code (KUHAP), yet still superficial, does regulate the mechanism for appointing an interpreter. This study aims to elaborate: first, the urgency of an interpreter during trial; and second, how the law regulates the existence of an interpreter assistance for defendants. This research uses a normative juridical method. Based on the problem mentioned above, the conclusion is as follows: First, the appointment of an interpreter aims to ensure equality between the defendant and the prosecutor. Those conditions will lead to a verdict based on substantive truth by the judge. Second, the judge must use an official decree to appoint an interpreter, granting them legal authority during the trial. Before the interpreter translates any facts in the trial, they must first take an oath or pledge. An interpreter who provides intentionally false translations will be charged under Article 242 of the Criminal Code. Additionally, an interpreter who has been appointed but fails to fulfill their duties can be penalized under Article 224 paragraph (1) of the Criminal Code, and if the interpreter unlawfully fails to appear, they can be penalized under Article 522 of the Criminal Code. This study recommends that future reforms of the Criminal Procedure Code explicitly state that judges should appoint interpreters through official decrees and interpreters should be certified and integrated into the criminal justice system.